Academic obituaries and posthumous tributes: scientific legacies for the field of Scientometry - Piumbato Innocentini Hayashi, Maria Cristina; Masson Maroldi, Alexandre; Massao Hayashi, Carlos Roberto (Revista General de Información y Documentación, 2021)
Academic obituaries and posthumous tributes are narratives that enshrine biographical trajectories of talent and merit. The aim of this article was to investigate how the scientific legacies of intellectual and inspirational leaders for the Scientometrics field are recognized by peers in academic obituaries and posthumous tributes. Theoretical and methodological contributions of the research come from Information Science and Sociology of Science. Through quantitative and qualitative categories, academic obituaries (n=48) and posthumous tributes (n=77) published in scientific journals were analyzed. By tracing the profile of the deceaseds, obituarists and obituaries, the study highlighted their main contributions to the field of Scientometrics and demonstrated that academic obituaries can provide important elements to reveal the scientific legacies and the inspirational impact of these researchers in their fields of knowledge.
Keywords: Academic obituaries; Posthumous tributes; Scientometry; Sociology of Science; Scientific recognition